Does Foreign Direct Investment Affect Industrial Workers? Evidence from Kingdom of Saudi Arabia - Khodeir, Aliaa Nabil; AL Nuwaiser, Sarah Nasser (International Journal of Economics and Financial Issues, 2016)
This paper aims at determining the essential variables that affect the employment of industrial workers in the kingdom of Saudi Arabia (KSA) by focusing on the role of foreign direct investment as an indicator of financial openness. By using the methodology of the Autoregressive Distributed Lag (ARDL) to identify the impacts on both the short and long run during the period (1990-2014), it turns out that foreign direct investment does not have a positive impact on the employment of industrial workers which is contrary to the hypothesis of the study. The empirical results have shown that there is a positive and significant impact of both exports and inflation on industrial employment on the long run only. Thus, the current paper is important in the decision making concerning investment and labor market in KSA. Keywords: Foreign direct investment, Industrial workers, Cointegration, ARDL, Saudi Arabia JEL Classifications: F21, F41, F66